Perfil, formação e atuação do docente em atividade permanente nos Programas de Pós-Graduação Stricto Sensu em Administração da região nordeste: um quadro-síntese a partir do currículo lattes - Silva, Hilda Lacerda da (2007)
This work shows, according to information of the curriculum Lattes, the profile of the professsors permanent of the Programs of after-graduation in Administration, recognized for the CAPES, located in the Northeast region of the Brazil, wich relation to the characteristics of the academic formation and the areas professional performance. In order to reach that goal a documental research was accomplished with exploratory research, once little information exists about that subject. The collected data on those curriculums were organized in a database and transferred to statistical treatment with the use of the statistical package SPSS - Statiscal Package Social Scienses for a quantitative evaluation. The analysis have been accounted according to the graduate and postgraduate formation. The study has involved the performance, presented disciplines areas, educational orientations and some aspects of the production and scientific popularization. Almost 50% of the educational ones around the researched universe are located among institutions of the Bahia State. Most of that group is formed of the masculine gender. They are 40,6% (39 individuals) the educational/researchers with lower graduation in Management and 37,5% (36 individuals) with lower graduation in other Areas. Around the educational/researchers masters 42,7% (41 individuals) which are mastered in Management. 20,8% (20 individuals) are assembled by educational with graduation and doctorate in Management, but there are among researchers' 10 and 50% depending on the researched variable, acting without a specific formation in the area. The graduate number and postgraduates in other areas overcome the number of educational graduate and postgraduates in Management area with relationship to the declared areas of performance, although with a small difference. The quantity of graduated and postgraduates educational ones from other areas outnumbers the graduated and postgraduates in Management with relationship to the declared areas of performance, although with discreet difference. The insert of graduated and postgraduates educational ones in Management to act in other Areas present a smaller percentile. The national periodical magazines like Organizations and Society, Ebape magazine and Contemporary Management Magazine (RAC), all of them classified the Qualis System as National A are the most used periodical ones for publication for their studies.